Osteossíntese umeral em pombos domésticos (Columba livia) com placas bloqueadas ou convencionais com e sem o uso de cimento ósseo - Campeiro Junior, Luiz Donizete (2019)
Fractures in birds present high prevalence in long bones of the wings, the use of osseous plates being limited by several factors, from the size of the implant, the weight of the animal and the type of fracture. For this study, 27 domestic pigeons (Columba livia) were used, separated into four groups randomly, with the objective of evaluating the healing and stiffness bone fractures of transverse fractures in medial diaphysis with different forms of treatments. In the blockade bone plate (POB) group, osteosynthesis was performed with bone plaque locked and bolts locked; in the conventional bone plate (POC) group to osteosynthesis was performed with conventional bone plate and cortical screws; in the bone plaque group conventional cement plus bone cement (POC + C) was used the same implant of the POC group plus the use of polymethylmethacrylate (PMMA) bone cement; and in the bone plaque group more bone cement (POB + C) was even implanted from the POB group plus PMMA. O The follow-up of each group was performed through flying activity being positive in all birds. After 120 days the animals were submitted to euthanasia and performed the biomechanical compression flexion test in three points. However, no statistically significant differences groups at the end of the experiment (p>0.05), and we can indicate the use of the plaque for pigeons, since it is an implant that has been shown not to have the need to modeling of bone to bone minimizing surgical time and nonuse of PMMA because it did not present any advantage in relation to the non-use and being an additional cost to the surgical procedure.